Development of a Telepresence Robot with Integration of a General Practice Medical Consultation Module - Carranza, Karmelo Antonio Lazaro R.; Day, Nicole Jillian B.; S. Lin, Lawrence Matthew; Ponce, Albert R.; Reyes, Wilbur Rex O.; Abad, Alexander C.; Baldovino, Renann G. (International Journal of Engineering and Technology, 2018)
The Philippines is facing a major problem in the healthcare industry—the maldistribution of doctors. This greatly affects people’s accessibility to proper healthcare; in fact, in 2015, 59.2% of deaths in the Philippines are attributed as deaths unattended by a doctor. One viable solution to this problem is the use of telepresence robots, as doctors can still provide quality healthcare services even when located in remote areas. The researchers developed a mobile telepresence robot integrated with different physical examination equipment used in general practice medical consultation, which are an otoscope with a tested average video delay of 3.76s over VPN, a stethoscope with 5.19s audio delay (LAN), and an ultrasound probe with 6.32s video delay (LAN). The teleconsultation system also consists of a web-based application, which serves as a medium for the duplex communication, remote robot control, patient database access, and transmission of media footage captured by the physical examination devices. The developed web-based application had an overall relative efficiency of 93.58% and a System Usability Scale Score of 82.5, when used by invited medical professionals. The researchers believe that this will extend the reach of medical doctors to rural areas and improve the overall health conditions in these communities.